2022
DOI: 10.1186/s12879-022-07806-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus infection in the Gulf Cooperation Council: a systematic review and meta-analysis

Abstract: Background Hepatitis B virus (HBV) infection is a global public-health problem. Since the introduction of an effective vaccine, the epidemiology of HBV infection is changing. We aimed to estimate the prevalence of HBV infection in the Gulf Cooperation Council (GCC) region and delineate any variation in member-countries, special sub-groups, and over time. Methods This is a systematic review and meta-analysis to review studies of HBV prevalence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Additionally, the prevalence of HBV infection in the MEA region (0.6–8%) is also higher than in Western Europe and North America (<1%), with the rate of infection being >4% among the GCC states [ 47 , 49 , 51 , 52 , 53 , 54 ]. Apparent HBV prevalence in the GCC region ranges from 0–3% in the UAE, 2–4% in Qatar, 0.5–5% in Kuwait, 3–4% in Saudi Arabia, 0–6% in Bahrain, and 2–6% in Oman [ 49 , 50 , 54 , 55 ]. HBV-induced pathogenesis of HCC involves several mechanisms, including HBV-DNA integration into host genetic machinery, DNA methylation, oxidative stress, and HBx protein [ 11 , 45 ].…”
Section: Epidemiology Of Hcc Across the Gulf Regionmentioning
confidence: 99%
“…Additionally, the prevalence of HBV infection in the MEA region (0.6–8%) is also higher than in Western Europe and North America (<1%), with the rate of infection being >4% among the GCC states [ 47 , 49 , 51 , 52 , 53 , 54 ]. Apparent HBV prevalence in the GCC region ranges from 0–3% in the UAE, 2–4% in Qatar, 0.5–5% in Kuwait, 3–4% in Saudi Arabia, 0–6% in Bahrain, and 2–6% in Oman [ 49 , 50 , 54 , 55 ]. HBV-induced pathogenesis of HCC involves several mechanisms, including HBV-DNA integration into host genetic machinery, DNA methylation, oxidative stress, and HBx protein [ 11 , 45 ].…”
Section: Epidemiology Of Hcc Across the Gulf Regionmentioning
confidence: 99%
“…G. lamblia is one of the eukaryotic parasites and causes Giardiasis, which is a common disease between humans and animals. The parasite infects the small intestine (jejunum and ileum) of humans (Rudolph et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, it is estimated that up to 20 million people are infected with giardiasis (Robertson et al, 2023). In a study conducted by researchers in 2022, it was found that the epidemic prevalence of giardia ranges between 2% and 50% in developing countries (Rudolph et al, 2022). Another study conducted in 2020 found that the epidemic prevalence of Giardia ranges between 5% and 20%, with the highest rates in countries with hot and humid climates (Machadol et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have connected OLP infection to hepatitis B and C to compare OLP patients with healthy controls to ascertain the prevalence of hepatitis C virus (HCV) antibodies and hepatitis B virus (HBsV) antigen [7]. Likewise, reported that 10% of the persons with lichen planus had hepatitis surface antigen, 15% had hepatitis B antibodies (vaccinated), and 9% had hepatitis C antibodies [9]. The possibility of recurrence of the disease is something that naturally concerns the patient to a great extent.…”
Section: Introductionmentioning
confidence: 99%